PENGEMBANGAN METODE ANALISIS BISAKODIL DAN FUROSEMID DALAM JAMU PELANGSING MENGGUNAKAN KROMATOGRAFI LAPIS TIPIS-DENSITOMETRI - Zaki Firdaus, Muhammad
Traditional herbal medicines have been commonly used in Indonesian society. According to the regulation of Ministry of Health of Indonesia Number 007/2012, the addition of isolated or synthesized chemical drugs in traditional herbal medicines is prohibited. However, adulterated traditional herbal medicines are often found and obtained easily. One kind of traditional herbal medicines that is often adulterated is slimming jamu product. Chemical drugs that have been reported used in slimming jamu products are bisacodyl and furosemide. The purpose of this research was to develop an analytical method for bisacodyl and furosemide in slimming jamu products. Both compounds were analyzed using Thin Layer Chromatography-Densitometry method. The mobile phase was n- hexane – ethyl acetate – propanol – acetic acid glasial (70:25:5:2.5). Calibration curve of bisacodyl had a linear equation of y = 3388.7x – 185.9 with r value of 0.9994. Calibration curve of furosemide had a linear equation of y = 4270.9x + 1134.7 with r value of 0.9997. The LOQ and LOD of bisacodyl were 0.196 ?g/spot and 0.065 ?g/spot respectively, while the LOQ and LOD of furosemide were 0.247 ?g/spot and 0.081 ?g/spot. Acuracy test of bisacodyl and furosemid showed recovery of 100.83% and 100.18% respectively. Intraday precision test showed the coefficient variation of bisacodyl were 2.73%, 2.56%, and 1.73%, while interday precision test showed the coefficient variation were 1.69%, 3.29%, and 3.30%. Intraday precision test showed the coefficient variation of furosemide were 1.35%, 1.26%, and 1.28%, while interday precision test showed the coefficient variation were 1.44%, 0.74%, and 1.25%. The analysis of 10 slimming jamu products showed no presence of bisacodyl and or furosemide in every sample.